History Makers: Polar Explorers - Currie, Stephen; Nang ChanYeema (California, USA Lucent Books, 2002)
Discusses the lives, education, successes, and failures of such explorers as John Franklin, Robert Peary, Matthew Henson, Roald Amundsen, and Robert Falcon Scott as they ventured into the Arctic and Antarctic.
Keywords: Adult Nonfiction